GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PERILAKU PENCEGAHAN PREEKLAMPSIA DI PUSKESMAS OEPOI KOTA KUPANG - Yuniyati Abineno; Maria Yasintha Goa; Yulia M.K Letor (STIKes CHMK, 2022)
Preeclampsia is one of causes of maternal and fetal mortality, with a high incidence. However, in fact there are still many pregnant women who don’t know how to prevent preeclampsia. The purpose of this study was to determine the factors associated with preeclampsia prevention behavior in pregnant at Oepoi Health Center, Kupang City. This research is a quantitative study with a correlative analytical research design using a cross sectional approach. The number of samples of this study were 167 respondents, using consecutive sampling technique. The inclusion criteria of this study were pregnant women who took an examination at Oepoi Public Health Center, Kupang City, willing to be a respondent, fully aware and able to answer all questions about her situation and pregnant women who can read and write. The results of this study indicate that most respondents have good knowledge, which is 115 respondents (68,9%,. The results statistical tests using Chi-square showed that there was no relationship between knowledge and preeclampsia prevention behavior in pregnant woman with a significant value 0,684 (ρ > 0,05), This study concluded is that there is not correlation between knowledge and preeclampsia prevention behavior at Oepoi Health center Kupang City. Keywords: Knowledge, Behavior Prevention, Preeclampsia